2022
DOI: 10.1246/cl.220081
|View full text |Cite
|
Sign up to set email alerts
|

Photo-on-demand Phosgenation Reactions with Chloroform Triggered by Cl2 upon Irradiation with Visible Light: Syntheses of Chloroformates, Carbonate Esters, and Isocyanates

Abstract: Chloroform (CHCl 3 ) upon bubbling with O 2 containing ³2% Cl 2 underwent oxidative photochemical conversion to phosgene (COCl 2 ) when exposed to a white LED light. Cl 2 may serve as a visible light-responsive radical initiator in the radical chain reactions of CHCl 3 and O 2 . This photochemical reaction allowed both in situ and stepwise one-pot phosgenation reactions, which are simple and safe methods, without expensive apparatus. It can be applied to a variety of conventional organic syntheses using phosge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…In support of this proposed mechanism, commercially available l -Phe·HCl was found to provide the corresponding NCA in 70% yield (Table , entry 1I). Thus, the reaction takes a longer time at higher temperature compared with other phosgenation reactions reported previously. For safe handling of the reaction, the generated amount of COCl 2 should be regulated by ON–OFF cycles and/or intensity of the photo-irradiation, and the vaporized COCl 2 and generated HCl must be trapped with alcohol and alkaline water.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In support of this proposed mechanism, commercially available l -Phe·HCl was found to provide the corresponding NCA in 70% yield (Table , entry 1I). Thus, the reaction takes a longer time at higher temperature compared with other phosgenation reactions reported previously. For safe handling of the reaction, the generated amount of COCl 2 should be regulated by ON–OFF cycles and/or intensity of the photo-irradiation, and the vaporized COCl 2 and generated HCl must be trapped with alcohol and alkaline water.…”
Section: Resultsmentioning
confidence: 99%
“…For example, carbonate esters and their intermediate chloroformates were synthesized in high yields only upon irradiation by UV-C light of CHCl 3 solutions containing an alcohol with or without an organic base . Furthermore, we recently reported that these photochemical reactions occurred with visible light in the presence of a small amount of Cl 2 . To cause the reactions, there were threshold concentrations of alcohol and base in the CHCl 3 solution (generally [CHCl 3 ] ≫ [base] > [alcohol]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We expect that it will contribute to the sustainable organic synthesis capable of reducing chemical waste and CO 2 emissions and will be used mainly in industry . For the academic purpose, however, it is preferable to use the in situ batch photo-on-demand phosgenation reactions reported mainly by our group for safety reasons. …”
Section: Discussionmentioning
confidence: 99%
“…As an alternative on-demand method to generate COCl 2 , we previously reported oxidative photochemical conversion of CHCl 3 to COCl 2 upon exposure to UV light with a batch reaction system. Although the reaction proceeds without chemical reagents, its efficiency with respect to the amount of CHCl 3 has not been clarified quantitatively. Herein, we studied a novel flow photochemical oxidation of CHCl 3 under precise control of the flow rates of CHCl 3 and O 2 and found that the reaction occurred efficiently in the gas phase in a short time to give COCl 2 in over 96% yield (Scheme b) .…”
Section: Introductionmentioning
confidence: 99%